Yield Study of Tea Tree Essential Oil Using Microwave-Assisted Process - Saoud, Amer Ali; Yunus, Rosli Mohd; Aziz, Ramlan Abd. (ASEAN Journal of Chemical Engineering, 2006)
There have been developments on the use of microwave to accelerate the digestion of solid materials, the heating of materials, and, more recently, the extraction of solute from solids via solvent as extracting medium. Microwave-assisted process (MAP) was used to accelerate the extraction of target compounds. It can be used for the extraction of compounds from various plant and animal tissues or of undesirable components from raw materials. Tea tree leaves were used in this study to investigate the applicability of microwave irradiation for essential oil extraction. The microwave parameters studied were tea tree leaves/ethanol ratio as well as required dose of microwave and time of irradiation. Different ratios of tea tree leaves/ethanol had been examined in order to obtain the optimal feed/solvent ratio that would give the highest yield of extracted essential oil. The required number of microwave doses that provided an accomplished extraction process had been ascertained. The optimal time of microwave exposure was found to be at 3 min. The measurements of extracted tea tree essential oil constituents (Le., cineole, a-pinene, and y-terpinene) that represent the major constituents were performed using gas chromatography (GC) analysis to estimate the yield of extracted tea tree essential oil.